Identification and Quantification of Quercetin, Naringenin and Hesperetin by RP LC – DAD in Honey Samples from B&H - Kurtagić, Harun; Redžić, Sulejman; Memić, Mustafa; Sulejmanović, Jasmina (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2013)
A large number of different products on the market comes under the name of honey, but many of them are false. Presence of flavonoids in the honey samples may be an indication of its origin. There for ethere is a need for reliable analytical methods for identification and quantification of flavonoids in the honey samples. Flavonoids as constituents of many plants, bees bringto the hive through pollen and honey dew. In this work, identification and quantification of three flavonoids: quercetin, naringenin and hesperetin from twelve honey samples of different botanical origin from Bosnia and Herzegovina were performed. The samples were collected during the period July-September, 2010. Reverse phase liquid chromatography coupled with diode array detector (RP LC-DAD) has been used to separate flavonoids and to quantify them in extractive solutions from honey samples. Results showed that the highest amount of quercetin (43.28 μg/100 g honey) and hesperetin (50.12 μg/100 g honey) was found in honey acacia (K2) and naringenin (41.40 μg/100 g honey) in the linden. The highest total content of all investigated flavonoids was 122.40 μg/100 g honey in sample of honey acacia (K2).